A facile one-pot synthesis of microspherical-shaped CoS2/CNT composite as Pt-free electrocatalyst for efficient hydrogen evolution reaction. (21st June 2019) - Senthil, Raja Arumugam; Wang, Yali; Osman, Sedahmed; Pan, Junqing; Lin, Yanjun; Shu, Xin; Jin, Xin; Sun, Yanzhi
Abstract: Hydrogen evolution reaction has been recognized as a green technology in the field of electrochemical energy conversion and storage devices. Nevertheless, it is necessary task to finding an economical and effective electrocatalysts for HER. Among the different HER catalysts, the cobalt disulfide (CoS2 ) showed an excellent HER activity owing to its low cost, easy to synthesize and good stability. Hence, in this work, we prepared a series of CoS2 /CNT composites with different contents CNT from 4 to 12 wt% by a simple one-step hydrothermal method to investigate the influence of CNT on HER activity of CoS2 . The structural and morphological properties of the obtained samples were analyzed through XRD, SEM, HR-TEM, and XPS. The SEM images of CoS2 /CNT composite showed the spherical-shaped CoS2 covered by the CNT nanostructure. In addition, the electrochemical tests were carried out using 0.5 M H2 SO4 solution in order to assess their HER activity. The attained electrochemical results showed that the CoS2 /CNT composite with 8% CNT offers an outstanding HER activity with the smallest overpotential of 155 mV at 10 mA cm −2 and lowest Tafel slope of 59 mV dec −1 when compared with other composites. Also, the optimized CoS2 /CNT composite provided excellent stability in the acidic medium after 1000 cycles. Therefore, the as-synthesized CoS2 /CNT composite will be an efficient, low-cost and Pt-free electrocatalyst for HER application. Graphical abstract: Image 1 Highlights: A low-cost CoS2 /CNT composite was synthesized via one-pot hydrothermal method. The CoS2 /CNT composite has a spherical-like morphology with better surface area. The CoS2 /CNT composite with 8% CNT showed a superb catalytic activity toward HER. This finding offered an outstanding Pt-free electrocatalyst for energy application.